2013
DOI: 10.2141/jpsa.0120134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics on the Localization of T Cell Subsets in the Intestine of Broiler Chicks

Abstract: The aim of this study was to determine the effects of probiotics on T cell subsets induction in the intestine of broiler chicks. Day-old male broiler chicks were fed with or without probiotics consisting of Streptococcus faecalis, Clostridium buthricum, Bacillus mesentericus (probiotics group and control group, respectively). Cryostat sections of their ileum, cecum and rectum at day 0, 7 and 14 of feeding were immunostained for CD4, CD8 and TCRγδ, and the frequencies of positive cells in the mucosal tissue wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…(Figs 5 and 6). Huang et al (2013) reported that probiotics enhanced the formation of pool of CD8 + T cells in the intestinal mucosa and also correlated with the results of Haghighi et al (2008) who reported that the elevation of CD8 + T cells density by probiotics treatment.…”
Section: Becton Dickinsonsupporting
confidence: 76%
“…(Figs 5 and 6). Huang et al (2013) reported that probiotics enhanced the formation of pool of CD8 + T cells in the intestinal mucosa and also correlated with the results of Haghighi et al (2008) who reported that the elevation of CD8 + T cells density by probiotics treatment.…”
Section: Becton Dickinsonsupporting
confidence: 76%
“…Recent studies demonstrated that probiotics can improve T cell subsets through regulation of gut microbiota ( 48 ). Huang et al ( 49 ) observed that combined probiotics consisting of Streptococcus faecalis, Clostridium buthricum , and Bacillus mesentericus can induce T cell subsets in the intestine of broiler chicks. These probiotics mainly cause an influx of CD8 + T cells into the intestinal mucosa; this influx may enhance intestinal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported that in chicken there were only a few CD4 + T cells in the intestine while CD8 + T cells predominate [ 21 ]. Similar to Huang’s report, we also found that CD4 + T cells represented minor proportions among the intestinal lymphocyte subpopulations since CD4 + /CD8 + ratios both in IELs and LPLs were less than 1.0 in all samples of both groups.…”
Section: Discussionmentioning
confidence: 99%